DAMPAK KONVERSI LAHAN PERTANIAN KE NONPERTANIAN TERHADAP SOSIAL EKONOMI MASYARAKAT DI DESA SITIMULYO, PIYUNGAN, BANTUL - Hasbi Fadholi; Agus Surata; Teguh Kismantoroadji (Jurnal Dinamika Sosial Ekonomi, 2015)
This study aims to analyze poverty, education and land prices directly affect the conversion of agricultural land to non-agricultural in Sitimulyo village, District Piyungan, Bantul and analyze poverty, education and land prices impact directly and indirectly to the social economy through the conversion of agricultural land to non farm in the village of Sitimulyo, Piyungan subdistrict, Bantul. This study uses qualitative research methods, with the kind  of descriptive analysis. The method to determine the location of the research using the case study method. The method of determining respondents were census. The data used are primary data and secondary data. Source data from this study is Monograph Village, the Village, relevant government institutions and study of literature. Data collection technique were interview and questionnaire. The analysis method is to use Path Analysis. The results of this study indicate that poverty, education and land prices have an indirect influence on the conversion of agricultural land to non-agricultural and poverty, education, land prices impact directly and indirectly through land conversion on social economic Sitimulyo village Piyungan District of Bantul. Keywords: poverty, education, land prices, land conversion and socio-economic